Deformation Process and Mechanism Analyses of a Rock Slope Based on Long-Term Monitoring at the Pubugou Hydropower Station, China. (13th February 2021) - Mei, Xuefeng; Wang, Nengfeng; Ma, Guotao; Wang, Jie; Wang, Yan; Wu, Jianli; Han, Mei; Cai, Bin
Abstract : This paper presents a typical 450 m high rock slope in a highly jointed and fractured rock mass at Pubugou (PBG) hydropower station on the Dadu River. We established a set of multiphase field geological survey combined with GPS, inclinometers, and piezometer monitoring system to analyze the deformation and failure mechanism of rock slope. The results show that small-scale excavation in road construction disrupted the balance of the Pubugou rock slope (PBGRS), and several local retrogressive failures occurred at the toe. Monitoring data regarding surface and subsurface movements show that the PBGRS is stable as a whole. The deformation concentrated mainly in the loosened fractured zone, which was a feature with sliding-compression cracking. Highly loosened rock mass was the predominant factor affecting the stability of the PBGRS, while the role of reservoir water level fluctuation, though positive, was not significant. Overall, the PBGRS still has a high potential for further development, especially in the slope's upper zone. To reinforce the slope, measurements mainly consist of the concrete frame combined with anchor cables constructed on the slope. In this study, the analysis was carried out of pre- and postreinforcement measure slope stability with numerical simulation, and safety factor increased from 1.09 to 1.21. This study's findings have important implications to the analytical method and reinforcement design with geological settings like that of the PBGRS.